Power Scenes in Four Theatrical Acts in Olmec Art from San Lorenzo Tenochtitlan, Veracruz, Mexico - Morante López, Rubén B. (2025)
Introduction: Cultural traits of the Olmec remain unknown due to their early appearance, the deterioration of their remains, and the limited presence of written records. Their social and economic organization has been inferred through Archaeology. Objective: Our central question investigates the narrative surrounding Olmec monumental art, specifically its thrones and colossal heads, since they responded not only to aesthetic interests, but also to religion and politics. Methods: In the introduction, we raise concepts such as long duration and power, essential to support our dissertation. We also present some data about the archaeological Olmecs, a conceptual framework for the analysis of the creations of thes epeople, where art is the vehicle that, throughout time and space, has communicated ancient civilizations with the present. Results: Art, as a means of communication, allows us to see and pose historical facts. Conclusions: Power is presented as a long, ideological performance whose aims range from legitimizing a governor to the arrival of those who overthrew him to leave a lasting message or to erase it.